PELAKSANAAN PROGRAM PROYEK KERJA MASYARAKAT (POKMAS) DI DESA LUBUK JERING KECAMATAN SUNGAI MANDAU KABUPATEN SIAK TAHUN 2012 - AL IKHLAS "; MUHAMMAD RIDWAN (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Along with be applied financial special Donation Program to POKMAS Village / sub-district at Regency Siak to insfrastruktur's development village / sub-district. insfrastruktur's development effort Village / this sub-district after make easy executed society by society bases Number Regent regulation 48 Year 2011 one be performed on each village / sub-district those are on Regency Siak. Base PERBUB that at Lubuk Jering's Village is performed Programs Society job Project (POKMAS) about development insfrastruktur year Village 2012. To the effect of observational it is subject to be know why Performing Program Society job Project (POKMAS) at Lubuk Jering's Village Year 2012 less maximal. Implementation concept that is utilized is concept that interposed by Edward III. which is implementation concept where exists four highlights which is communication, resource, executor attitude and bureaucracy structure. Tech that is utilized in data collecting utilizes interview and documentation tech.After do research therefore writer can conclude that four big influential implementation highlights deep POKMAS'S performings Lubuk Jering's Villages years 2012. Of research result is concluded that was optimal Performing Process Programs since adverse coordination among village government with society so executed development was utterly entirely. Communication that is done was clear and consistent. Of proprietary resource facet was enough even there are some lack as reducing its field executor staff as tip of POKMAS'S performing spear this. Facility that gave by regency party no since POKMAS'S performing performed by modestly and self-supporting is society, Regency party just provide donation fund. Of cendrung's attitude facet not blocks since executors have the honour and have willingness.Factor that constrain in performing Programs POKMAS slowing lents fund to get down from regency so program performing rather its finish long time, because of other fund that is used no so the execution enforced wait that regency2fund is downwards goes to village and other constraint which is in POKMAS'Sperforming which is if one of village at silvan troublesome district another onealso following most constraint and development fund of slightly long timeregency until it to executor that POKMAS'S performing rather its finish long time.Key word : mobilization, consciousness, conflict, person is official, society